Crowfunding Financing in the View of Islam - Nanik Eprianti; Mohammad Andri Ibrahim; Popon Srisusilawati (al-Afkar, Journal For Islamic Studies, 2024)
The presence of financial technology in the financial institution industry is growing very rapidly. Crowdfunding is one of the ways for Muslims to plant kindness in the form of helping each other by means of charity jariyah for the needs of social charity which will be a charity of goodness for the afterlife. The purpose of the analysis is to see the suitability of Islamic crowdfunding financing, and what is the Islamic view of crowdfunding financing. This research uses qualitative methods using a descriptive analysis approach. The types of data used in this study are secondary data and literature research. The result of this research is that sharia crowdfunding financing is one of the innovations of financial institutions in improving financial services for the community. The concept of sharia crowdfunding applied in Indonesia is already guided by the Qur'an and Sunnah, this can be seen in the existence of a sharia supervisory board that oversees the financing process, in accordance with the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) Number 117 / DSN-MUI / II / 2018.